Histological changes of endocervical polypoid lesions in women at reproductive age - Muna Zuhair Al-Hamdany; Mustafa Salah Fadhil (Medical Journal of Babylon)
Abstract Background: Endocervical polyps (ECP) are fragile benign protrusions commonly affecting 2%–5% of women during the reproductive age. Aim: This study aimed to identify the histopathological changes of clinically identified endocervical polypoid lesions during the reproductive age to detect any premalignant or malignant transformation if present. The objective is to assist the clinicians to decide whether the cervical polyps should be excised or not. Materials and Methods: Sixty specimens of the resected cervical polyps were obtained from Al-Salaam Teaching Hospital in Mosul city during the period from June 2021 to February 2022, women diagnosed to have cervical polyps on per speculum examination were given a time to be operated on with exclusion of pregnant, postmenopausal women, those on hormone replacement therapy, and those below 20 years. After polypectomy, fixation of biopsies in 10% buffered formalin was done followed by processing and staining with hematoxylin and eosin for histological examination. Chi-square test was used for interpretation of the histological findings. Results: The study revealed that 52% of the enrolled women were in the range of 40–49 years of age. Squamous metaplasia and benign microglandular hyperplasia were detected equally in 25% of the study group. Nabothian cyst was observed in 8%, whereas leiomyoma presenting as cervical polyp in 6%. Fortunately, no malignant changes were reported in the examined 60 cases and the only serious lesion was cervical intraepithelial neoplasia (CIN) observed in 2% of the examined polyps. Conclusion: we conclude as the incidence of malignant transformation of endocervical polyp is low in women in reproductive age and the only critical lesion is in situ intraepithelial neoplasia (CIN), it is proposed to follow an expectant management without interference and those patients can be only followed up to improve their health.